2021
DOI: 10.2147/idr.s307488
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Xpert MTB/RIF Accuracy for Detecting Rifampin Resistance in Bronchoalveolar Lavage Fluid on Bacterial Load: A Retrospective Study in Beijing, China

Abstract: Introduction We assessed the effect of Mycobacterium tuberculosis (MTB) bacterial load on Xpert MTB/RIF accuracy for detection of rifampicin (RIF)-resistant MTB in bronchoalveolar lavage fluid (BALF) specimens obtained at a national tuberculosis (TB) specialized hospital in Beijing, China. Methods A retrospective study was conducted at Beijing Chest Hospital. Patients with symptoms suggestive of pulmonary TB who provided BALF specimens for rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…In 2016, Ocheretina et al investigated 22 TB patients, revealing that the Xpert test was more likely to produce false-positive results for RIF-R in clinical samples with extremely low bacterial loads [ 19 ]. Subsequently, studies from Beijing, China, and Rwanda have confirmed this finding [ 21 , 22 ]. In contrast, Berhanu et al, using “medium” load as a reference, revealed similar levels of discordance as observed in “very low” samples, using Xpert testing (IRR = 1.22, 95 % CI 0.4–3.70) [ 13 ].…”
Section: Discussionmentioning
confidence: 80%
“…In 2016, Ocheretina et al investigated 22 TB patients, revealing that the Xpert test was more likely to produce false-positive results for RIF-R in clinical samples with extremely low bacterial loads [ 19 ]. Subsequently, studies from Beijing, China, and Rwanda have confirmed this finding [ 21 , 22 ]. In contrast, Berhanu et al, using “medium” load as a reference, revealed similar levels of discordance as observed in “very low” samples, using Xpert testing (IRR = 1.22, 95 % CI 0.4–3.70) [ 13 ].…”
Section: Discussionmentioning
confidence: 80%
“…According to recent reports, the MTB/RIF assay performed poorly and displayed higher variability when used to detect RR-MTB among samples with very low MTB bacillary loads. 5,6 Ngabonziza et al suggested that RR-positive tests should be repeated with a second sample, and whenever inconsistent initial and repeat MTB/RIF test results were reported, false-positive RR-TB should be ruled out before treatment initiation. 7 In the present study, Ultra was used, which is apparently unaffected by very low bacillary loads.…”
Section: Discussionmentioning
confidence: 99%
“…La tuberculose est une maladie infectieuse causée par le Mycobacterium tuberculosis, capable d'affecter tous les tissus humains [1], [2]. Elle demeure à ce jour un problème de santé publique, avec 10,6 millions des cas notifiés (une nette augmentation par rapport à 2020) et 1,6 millions de décès en 2021 [3], [4].…”
Section: Introductionunclassified
“…Pour y arriver, il faut des tests rapides et précis recommandés par l'OMS : BACTER MGIT 960 SIRE, Geno Type MTBDR Plus, Xpert MTB/RIF[64],[65]. Il faut cependant souligner des faux résultats de résistance des médicaments d'usage dans la lutte contre la tuberculose au GeneXpert qui ont été soulignés par certaines auteurs[2],[66]-[69], d'où la politique de prudence par des tests moléculaires répétés pour retenir des vrais cas de résistance à la Rifampicine. Pour Ngabonziza et al[67] au Rwanda, Beylis et al[70] en Afrique du Sud et Liu et al[71] en Chine, les faux résultats de la TB-RR seraient en rapport avec les cas de tuberculose pulmonaire pauci bacillaires.…”
unclassified
See 1 more Smart Citation